Design of a Device for Utilizing Hazardous and Toxic Waste as Fuel For a Stove (Burner) with a PID Control System - Weny Findiastuti; Ach Dafid; Rullie Annisa (Universitas Ahmad Dahlan, 2023)
Used oil waste is treated by spraying oil into the combustion furnace using wind from a blower. Before pouring oil into the furnace, it is necessary to manually heat it up to 300°C to burn off the fat. The controls in this study control the valve and blower to reach the desired temperature up to 800°C by utilizing a k-type thermocouple temperature sensor to detect temperature. This burner stove research uses the PID control method because it has a response that is fast enough to reach the desired temperature. The PID method is a controller that can reduce the error rate in a system to provide an output signal with a fast response, small error rate, and small overshoot. One of the contributions to this research is the importance of reducing the negative impact of hazardous and toxic waste on the environment and being an alternative solution in dealing with hazardous and toxic waste. In other conditions, this research makes an important contribution to the development of technology for processing and utilizing hazardous and toxic waste materials. Hopefully, this research will help contribute ideas and thoughts on preserving the environment and utilizing existing resources more efficiently. From the results of this study, based on the number of test results from seven tests, it can be said that the conditions are optimal because the fire produced from used oil does not contain black smoke. Meanwhile, the maximum temperature generated was 809 °C at the 73rd second, and the temperature continued to fall at the 94th second, and so on until it reached stability. These conditions indicate that the fuel speed ratio (used oil) and applied air pressure have started to improve so that the temperature is stable at 806 °C. In conclusion, the optimum test results at a flame temperature of 806 °C, the resulting flame does not produce black smoke, so the combustion of the used evaporative lubricant produces much cleaner exhaust emissions.